Penggunaan Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga Pada Kekerasan Dalam Pernikahan di Bawah Tangan (Studi di Pengadilan Negeri Malang) - Muhammad Ridlo Rizki Tsanian; Idaul Hasanah; Ratri Novita Erdianti (Universitas Muhammadiyah Malang, 2021)
This research describes and examines the opinion of the Malang District Court Judge regarding the use of Law Number 23 of 2004 concerning elimination of domestic violance on unregistered marriages. The existence of several previous court ruling with different results is increasing a question related to this problem. Many people, especially Moslems, are ignored the danger of unregistered marriages because they think it is legal in their religion. This research is a qualitative research, with the type of empirical research or field research by interviewing Malang District Court Judges, which is then analyzed using provisions constitutions through various sources. The results of the research show that unregistered marriage is a marriage that has never existed in the eyes of the state, likewise with households born from unregistered marriages. It is clear that this is not in accordance with the mandate of the constitutions. The previous court ruling does not have to be followed by a judge in deciding the case.